Pushing Forward West Nile Virus Understanding: An Integrated One Health Genomic Surveillance Journey in Romagna (Italy) - Miss Martina Brandolini; Dr Alessandra Mistral De Pascali; Mr Giorgio Dirani; Ms Silvia Zannoli; Ms Irene Zaghi; Ms Ludovica Ingletto; Dr Antonio Lavazza; Dr Davide Lelli; Dr Michele Dottori; Dr Mattia Calzolari; Mr Massimiliano Guerra; Dr Carlo Biagetti; et al. (International Journal of Infectious Diseases)
Introduction: In Italy, despite the existence of an epidemiological surveillance system for Arboviruses, managed in a One Health perspective, the implementation of genomic characterisation remains fragmented and no systematic genomic surveillance initiative integrating human and animal data has been established. The purpose of this study is to investigate the contribution of Whole Genome Sequencing (WGS) in the integrated genomic characterization of West Nile virus in target avian reservoirs, mosquito vectors and infected humans in Romagna (northeastern Italy). Methods: The study was conducted in Romagna, northeastern Italy, between May and October 2023 involving patients with encephalitis/meningitis and healthy blood donors who tested positive for WNV during screening programmes. Mosquitoes were sampled with attractive traps, and resident and migratory birds were collected as of active or passive surveillance. Samples were screened with WNV-specific PCR (Polymerase Chain Reaction) assays, and positive samples were subjected to WGS by tagmentation and hybrid-capture-mediated target enrichment (Viral Surveillance Panel, Illumina). Assemblies and consensus sequences were obtained with Bowtie2 v.2.4.1 and BCFtools. Maximum likelihood trees for viral phylogenetic inference were constructed with IQ-TREE 2.0.3 with automatic selection of the best nucleotide substitution model, 1000 ultrafast bootstrap replicates and midpoint rooted. Results: Eleven WNV lineage 2 sequences were obtained (4 meningitis cases, 3 blood donors, 3 Culex pipiens and 1 Pica pica). Genome sequencing yielded 98.8-100% coverage. Coding sequences maintained high nucleotide and deduced aminoacid conservation, with an average identity of 99.82% and 99.92%. Mutations of virulent clade 2d were identified, affecting infection rates in avian hosts and mosquito vectors and neuroinvasiveness in humans. Obtained sequences clustered within the Central-Southern European clade with robust bootstrap support, forming a distinct cluster with other viruses isolated in Italy from 2021 to 2023. Discussion: Our study, albeit with preliminary and limited results, provides an insight into integrated genomic characterisation of WNV strains circulating in the study area, where WNV is endemic and which is considered a high-transmission-risk hotspot due to its geoclimatic characteristics and its proximity with one of the main stop-overs and breeding ground for migratory birds in Central and Southern Europe (Delta of Po river). Continued genomic surveillance, throughout future seasons, will support the tracking of arboviruses genetic diversity, evolution, emergence of new variants or introduction of genetically diverse strains. Conclusion: Our approach suggests the importance of adopting an interdisciplinary multistakeholder strategy to integrate the steps from clinical diagnosis to entomological and ornithological monitoring, up to epidemiological and genomic surveillance to create an operational process involving human and animal health suitable for the genomic characterisation of both autochthonous and imported Arboviruses. Engaging both human and animal health sectors, will facilitate a comprehensive characterisation of endemic and emerging Arboviruses to mitigate their impact on public health.